Hyalinizing clear cell carcinoma of the soft palate - a case report - Syed Ahmad Fauzi, Sharifah Intan Safuraa Shahabudin; Subha, Sethu Thakachy; Doi, Mohamad; Adzman, Sellymiah (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2020)
Hyalinizing clear cell carcinoma presents as a painless submucosal mass commonly located at the palate and base of tongue. It is a rare tumour and has often been misdiagnosed for other more common tumours with clear cytoplasm, such as acinic cell carcinoma, clear cell oncocytoma or mucoepidermoid carcinoma. HCCC has been reported as a low grade malignant tumour with a high rate of cervical metastases. Due to its rarity, there is no treatment protocol. However, the treatment of choice is wide local excision and the neck disease is treated with neck dissection or radiotherapy or both with no conclusive outcome as incidence is too low or underreported with no long term follow up. Our case highlights the diagnosis difficulties in such rare cases, and the need for longer follow up post excision to determine outcome and recurrence rates.